Evaluation of growth and silk quality produced by Samia cynthia ricini (LEPIDOPTERA: SATURNIIDAE) fed different leaves - Refda Maulana Trisuji; Tri Atmowidi; Windra Priawandiputra; Yuni Cahya Endrawati (Penerbit Universiti Kebangsaan Malaysia, 2024)
Samia cynthia ricini Donovan (Lepidoptera), commonly known as the eri silkworm, is spread in India, Japan, China, and Indonesia. Previous research showed that silk quality produced by the species is comparable to mulberry silk. The eri silk has many generations per year (multivoltine) and feeds on several species of plants, making them easy to cultivate. The larvae consist of five instars, and each instar needs 3-7 days, and the pupa stage is 7-9 days, while the adults can live for up to seven days. In this study, the effect of different feeds, i.e., Manihot glaziovii Mull. Arg., Manihot esculenta Crantz, Cnidoscolus aconitifolius Miller I. M. Johnston and Terminalia catappa Linn. on larval growth and silk quality of S. ricini was examined. The mating duration and oviposition of moths were also studied. Observations consist of larvae and pupae growth, silk quality, adult characteristics, mating duration and oviposition. The results showed the length and the weight of the larvae among treatments were significantly different (P<0.05), except the larvae fed by M. glaziovii and M. esculenta (P=0.078 and P=0.38). Meanwhile, the cocoon length and weight and fiber tensile strength and diameter among treatments were not significantly different (P>0.05). The head, thorax, and abdomen lengths between feed treatments in male and female showed no significant difference (P>0.05). Meanwhile, the forewings and hindwings length of male and hindwings length of female between treatments differed significantly (P<0.05). The stage of mating behavior consists of calling, courtship, copulation, and oviposition. Total mating duration among treatments showed that each feeding treatment was not significantly different (P>0.05). Manihot glaziovii feed treatment also showed the highest fecundity (70-290 eggs), while the lowest eggs fecundity was in Terminalia cattappa (66-279 eggs).